Core aquatic environment remote data logging platform for aquaculture applications - Barrera, Christine Ann D.
Many Aquatic Environment studies have been done in the Philippines. Most of the methods used in these studies, specifically those that involve data gathering, are done manually or use expensive equipment. The development of a Remote Data Logging Platform for such studies can improve the state of Aquatic Environment Research done locally in terms of data accuracy, data gathering time, and cost. Current ocean monitoring for coral reefs, giant clams and sea grasses here in the country makes use of the above methods, thus this project proposes a CoRe approach, using four major blocks interleaved yet at the same time self-contained in operation. These four blocks developed as an Aquatic Environment Platform that can aid in measuring a variety of parameters involved in monitoring these natural resources. The four blocks are as follows: (1) the Underwater Logger, tasked to gather data from various sensors (eg. temperature and light) and store data in a Multimedia Card (MMC), (2) the Surface Logger, attached on the buoy to collect sensor data and make it available in two ways: wireless communication and MMC, (3) the Surface Tracker System, composed of a GPS-equipped device and a remote base station with GUI and database for easy data visualization and archiving, and (4) the Renewable Energy-Based Power System which provides power to all the blocks. The system was deployed twice in an actual test site for seagrass study in Pagbilao, Lucena to monitor temperature and light changes. The system was able to acquire data successfully including latitude, longitude, light and temperature (underwater, surface and ambient). This data from the CoRe system was compared to the data from manual monitoring of the Marine Science Institute (MSI) and the trends were the same. This proves that the CoRe system can serve as a useful aid in marine research.